Learning Management Self Regulated Learning Early Childhood Based Child Friendly - Elyana, Luluk (ACIECE, 2016)
Learning management is management that consists of planning, organizing, briefing, and controlling in terms of why and how human undergo behavior changes as a result of experiences. Essentially, early childhood learning is curriculum development that tangible which contain some learning experience through playing. One of the importance of the learning process in PAUD has Self Regulated Learning (SRL) that will put the urgency of the children’s ability to learn discipline to organize, self- control, and study with their own initiative. To put out this initiation, one of the processes is the concept of Ramah Anak (child-friendly) which is understanding the meaningfulness of the children. The teacher should place herself to be a facilitator and a motivator by understanding the uniqueness that the children have that will show because of individual differences. This is due to family background, ethnic, language, and culture differences in children not same. The children will have a sense of empathy and always proud to identify the knowledge that appears from the differences. For example, played a harvest festival with Madura's traditional clothes or dancing an Aceh traditional dance with Aceh traditional clothes accompany by their traditional songs. The children are given the freedom to initiate and the opportunity to express their opinion about the learning activity and the activity that will be performed next. For the management of child-friendly learning SRL in early childhood should be applied as an effort for the early development of the children development in cultivating a sense of empathy and the potential that the children have through positive habits and awareness to do well in their own work and appreciate the differences.